Pyrophosphate cross-linking agent and preparation method thereof, semi-solid electrolyte and battery

By using a symmetrical structure pyrophosphate crosslinker containing bisphosphine atoms in the semi-solid electrolyte, combining acrylate monomers and electrolytes for polymerization, the semi-solid electrolyte in the prior art has been solved in terms of flame retardant and electrical properties of semi-solid electrolytes in the prior art. The disadvantages of the battery achieve high safety and good electrochemical performance.

CN119481258AActive Publication Date: 2025-02-18XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411608074.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing semi-solid electrolytes have shortcomings in flame retardant and electrical properties, and it is difficult to improve the safety and electrochemical properties of the battery at the same time.

Method used

Using a pyrophosphate crosslinking agent with a symmetric structure containing bisphosphine atoms, it is applied to semi-solid electrolytes through a specific preparation method, and polymerization reaction is carried out in combination with acrylate monomers and electrolytes to form good flame retardant and electrical properties of electrolytes.

Benefits of technology

The battery has achieved good flame retardant performance and electrochemical performance. The first week of 0.2C reaches 100mAh/g or above. The capacity retention rate is high after 500 weeks of circulation, and it has high safety and electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130171750000021
    Figure BDA0005130171750000021
  • Figure BDA0005130171750000031
    Figure BDA0005130171750000031
  • Figure BDA0005130171750000032
    Figure BDA0005130171750000032
Patent Text Reader

Abstract

The invention relates to the technical field of semi-solid electrolyte, in particular to a pyrophosphate cross-linking agent, a preparation method of the pyrophosphate cross-linking agent, semi-solid electrolyte and a battery. The pyrophosphate cross-linking agent is a phosphate cross-linking agent which has a symmetrical structure and contains double phosphorus atoms, and when the pyrophosphate cross-linking agent is applied to a semi-solid electrolyte, not only is a good flame-retardant effect achieved, but also the 0.2 C first-cycle capacity of a battery prepared from the pyrophosphate cross-linking agent reaches 100 mAh / g or above, the capacity retention rate is high after 500 cycles, and good electrical performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semi-solid electrolytes, and in particular to a pyrophosphate cross-linking agent and a preparation method thereof, a semi-solid electrolyte and a battery. Background Art

[0002] With the frequent occurrence of battery fire accidents, how to improve the safety performance of batteries has become the current research focus. Traditional liquid batteries contain a large amount of free liquids. These liquids have disadvantages such as high volatility, low flash point, and easy leakage, which can easily cause safety accidents such as battery combustion and explosion. In order to make up for the shortcomings of commercial liquid electrolytes, people have taken a lot of measures: 1) Introducing flame retardant additives into commercial liquid electrolytes to enhance the flame retardant properties of batteries; 2) Replacing liquid electrolytes with all-solid electrolytes or semi-solid electrolytes. Among them, only introducing flame retardant additives into liquid electrolytes has very limited ability to inhibit battery combustion; and all-solid electrolytes have electrical performance defects such as large interface resistance and poor lithium ion transmission performance, which are difficult to commercialize; therefore, at this stage, semi-solid electrolytes are most likely to replace commercial liquid electrolytes.

[0003] Introducing flame retardant groups into semi-solid electrolytes can further improve the safety performance of batteries. Phosphate-based organic matter is a common flame retardant. On the one hand, phosphate decomposes when heated to form a mucous film of phosphoric acid and polyphosphoric acid on the surface of the material, thereby achieving a flame retardant effect; on the other hand, phosphate produces a large number of phosphorus oxygen free radicals when heated, which can combine with hydrogen free radicals and hydroxyl free radicals and quench them. Applying phosphate-based organic matter to semi-solid electrolytes can further enhance the safety performance of batteries and has become a hot topic in current research. However, the currently prepared phosphate-based semi-solid electrolytes mainly include TAEP, PFTnGA, (M)AnEPP, (M)AnEMP, etc. These electrolyte structure fragments contain only one phosphorus atom, and the flame retardant effect is limited.

[0004] The patent document with publication number CN111499663A discloses a phosphate cross-linking agent and a preparation method thereof, a phosphate-based cross-linked gel polymer electrolyte and a preparation method and application thereof. In some embodiments, spiropentaerythritol diphosphoryl chloride and an acrylate compound are used to prepare a phosphate cross-linking agent containing diphosphorus atoms. This cross-linking agent is added to a sodium ion liquid electrolyte at a certain concentration to have flame retardancy, but the electrical properties, such as specific capacity, and flexibility need to be improved.

[0005] There is also a patent document with publication number CN104380519A that discloses such a secondary battery, whose electrolyte contains a phosphate-based compound as an additive. In some embodiments, the phosphate-based compound is a pyrophosphate-based acrylate. The electrolyte using this additive also needs to add a flame retardant to improve the flame retardancy, indicating that its own flame retardant effect is not good. In addition, the pyrophosphate-based acrylate is acidic, which will not only induce the dissolution of transition metals in the positive electrode material and the loss of positive electrode active materials, but also promote the continuous decomposition of the SEI film, which is not conducive to the formation of a stable interface SEI film. Both of these effects will reduce the cycle performance of the battery. Summary of the invention

[0006] The present invention aims to solve the above problems and provides a pyrophosphate crosslinking agent having good flame retardancy and electrical properties and a preparation method thereof, a semi-solid electrolyte and a battery.

[0007] The technical solution of the present invention to solve the problem is: first , providing a pyrophosphate crosslinking agent, characterized in that it is a compound with the following structural formula:

[0008]

[0009] The present application provides a symmetrically structured phosphate cross-linking agent containing two phosphorus atoms. When used in a semi-solid electrolyte, it not only has a good flame retardant effect, but also the battery prepared therefrom has a 0.2C first-week capacity of more than 100 mAh / g, a high capacity retention rate after 500 cycles, and good electrical properties.

[0010] The inventor speculates that this may be because the spiro ring in the structure is removed while retaining the symmetrical structure and the diphosphorus atom. In terms of electrical properties, the spiro ring has structural rigidity and stability, which may limit the movement and distribution of charge inside the spiro ring, affecting the electrochemical properties of the material; it may also be due to the fact that the diphosphorus atoms in the present application are connected by oxygen groups, and the oxygen groups have strong polarity and are easy to interact with other polar molecules or ions, which is conducive to the accumulation and release of charge and improves the electrochemical properties of the material. In terms of flame retardancy, in addition to the effect of the diphosphorus atom, the high molecular weight compound of the symmetrical structure may not be easy to migrate, has good thermal stability, and has a strong endothermic effect, which helps to improve the flame retardant effect.

[0011] Here, n is a natural number and n≥0, for example, n can be 0, 1, 2, 3, 4, 5, etc.

[0012] As a preferred embodiment of the present invention, n=3; when n=3, the obtained pyrophosphate crosslinker is used in a battery, and the battery has the best electrical performance and flame retardant performance. This may be because a certain length of ethoxy chain segment is conducive to the transmission of ions, but the larger the n value, the smaller the proportion of the phosphate flame retardant segment, the flame retardant effect is inhibited, and the safety performance of the battery is weakened as the n value increases.

[0013] R is hydrogen or methyl, and the difference of R group has no effect on the electrical performance of the battery.

[0014] Secondly The present application also provides a method for preparing the above-mentioned pyrophosphate cross-linking agent, comprising the following steps:

[0015] S1. In the presence of an acid scavenger, reacting an ethylene glycol compound and an acryloyl chloride compound in a solvent to obtain an intermediate product;

[0016] S2. In the presence of an acid scavenger, reacting the intermediate product with pyrophosphoryl chloride in a solvent to obtain the pyrophosphate crosslinking agent.

[0017] In step S1 , ethylene glycol compounds are compounds with oxygen atoms and hydroxyl groups connected to ethyl groups, and their general structural formula is as follows:

[0018]

[0019] As mentioned above, n is a natural number and n≥0. As a preferred embodiment of the present invention, the glycol compound is selected from at least one of ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and hexaethylene glycol. Further preferred embodiment of the present invention, as mentioned above, n=3, that is, tetraethylene glycol is preferably used as the raw material.

[0020] The general structural formula of acryloyl chloride compounds is as follows:

[0021]

[0022] As mentioned above, R is hydrogen or methyl. As a preferred embodiment of the present invention, the acryloyl chloride compound is selected from at least one of acryloyl chloride and methacryloyl chloride.

[0023] The reaction equation involved is:

[0024]

[0025] The acid scavenger is used to neutralize the acidic byproducts such as HCl produced by the reaction. As a preferred embodiment of the present invention, the acid scavenger is selected from at least one of triethylamine, potassium carbonate, sodium carbonate, pyridine, and N,N-dimethylaniline. In order to avoid the introduction of impurities, as a further preferred embodiment of the present invention, the acid scavenger is triethylamine.

[0026] In the reaction, the acid scavenger needs to be in an appropriate amount, and the ethylene glycol compound needs to be in an excessive amount. As a preferred embodiment of the present invention, the molar ratio of the ethylene glycol compound, the acryloyl chloride compound, and the acid scavenger is (1.1-2):1:1. For example, it can be 1.1:1:1, 1.2:1:1, 1.3:1:1, 1.4:1:1, 1.5:1:1, 1.6:1:1, 1.7:1:1, 1.8:1:1, 1.9:1:1, 2.0:1:1; preferably 1.5:1:1.

[0027] In this reaction, since acrylic acid chloride compounds are highly active, as a preferred embodiment of the present invention, during operation, acrylic acid chloride compounds are slowly dripped into the mixed solution of ethylene glycol compounds and acid scavengers to avoid excessive local concentrations due to excessive addition at one time and side reactions.

[0028] In the reaction, the reaction environment temperature is preferably low temperature to prevent unnecessary conversion of sensitive functional groups in the reactants, avoid volatilization of the reactants, slow down the reaction rate, make the reaction more controllable, and reduce the occurrence of side reactions. As a preferred embodiment of the present invention, the reaction environment temperature is 0 to 10°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C; preferably 4°C.

[0029] In the reaction, the solvent should be stable and can dissolve the ethylene glycol compound and the acryloyl chloride compound well to ensure that the reactants are fully mixed and contacted in the solvent. As a preferred embodiment of the present invention, the solvent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, and ether. Further, as a preferred embodiment of the present invention, the solvent is tetrahydrofuran.

[0030] After the reaction, the intermediate product obtained should be washed and purified before being used in step S2. As a preferred embodiment of the present invention, after the reaction is completed, the mixed system is washed with water and dichloromethane solvents in sequence, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final intermediate product.

[0031] In step S2 , the reaction equation involved is:

[0032]

[0033] In the reaction, the acid scavenger is also used to neutralize the acidic byproducts such as HCl produced by the reaction. As a preferred embodiment of the present invention, the acid scavenger is selected from at least one of triethylamine, sodium carbonate, potassium carbonate, pyridine, and N,N-dimethylaniline. In order to avoid the introduction of impurities, as a further preferred embodiment of the present invention, the acid scavenger is triethylamine.

[0034] In the reaction, the acid scavenger needs to be in an appropriate amount and the intermediate product needs to be in excess. As a preferred embodiment of the present invention, the molar ratio of the intermediate product, pyrophosphoryl chloride, and the acid scavenger is (2.5-3.5):0.5:2. For example, it can be 2.5:0.5:2, 2.6:0.5:2, 2.7:0.5:2, 2.8:0.5:2, 2.9:0.5:2, 3.0:0.5:2, 3.1:0.5:2, 3.2:0.5:2, 3.3:0.5:2, 3.4:0.5:2, 3.5:0.5:2; preferably 3:0.5:2.

[0035] In the reaction, the reaction environment temperature is preferably low temperature to prevent unnecessary conversion of sensitive functional groups in the reactants, avoid volatilization of the reactants, slow down the reaction rate, make the reaction more controllable, and reduce the occurrence of side reactions. As a preferred embodiment of the present invention, the reaction environment temperature is 0 to 10°C, such as 0°C, 1°C, 2°C, 3°C, 4°C, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C; preferably 4°C.

[0036] In the reaction, the solvent should be stable and can dissolve the intermediate product and pyrophosphoryl chloride well to ensure that the reactants are fully mixed and contacted in the solvent. As a preferred embodiment of the present invention, the solvent is selected from at least one of dichloromethane, tetrahydrofuran, chloroform, and ether. Further, as a preferred embodiment of the present invention, the solvent is tetrahydrofuran.

[0037] After the reaction, the obtained pyrophosphate crosslinker should be washed and purified. As a preferred embodiment of the present invention, after the reaction is completed, the mixed system is washed with water and dichloromethane solvents in sequence, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final pyrophosphate crosslinker.

[0038] Secondly Another object of the present invention is to provide a semi-solid electrolyte using the above pyrophosphate crosslinking agent. The semi-solid electrolyte is prepared by the following steps: mixing the above pyrophosphate crosslinking agent with an acrylate monomer, an electrolyte, and an initiator to obtain a precursor, and initiating a polymerization reaction of the precursor to obtain an electrolyte.

[0039] In this application, the above-mentioned pyrophosphate crosslinking agent is used to obtain a semi-solid electrolyte, which is less likely to react with the electrode than the current liquid electrolyte, and will not leak to cause safety accidents, has good flame retardant properties, and has high safety. At the same time, compared with some semi-solid electrolytes in the prior art, it has been improved in flexibility and electrical properties.

[0040] Acrylic acid ester monomers are used to complement the electrochemical and mechanical properties of pyrophosphate crosslinkers to improve overall performance. The selection of acrylic acid ester monomers is not limited, as long as they can be used in electrolytes and can be polymerized. As a preferred embodiment of the present invention, the acrylic acid ester monomer is selected from at least one of methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethyl ethyl acrylate. Further, as a preferred embodiment of the present invention, the acrylic acid ester monomer is selected from methyl acrylate.

[0041] The amount of pyrophosphate crosslinker and acrylate monomer should be limited. If the content of pyrophosphate crosslinker is too high, the electrolyte elasticity and toughness are insufficient and the stability is poor, resulting in reduced electrical performance (capacity retention rate after 500 cycles); if the content of pyrophosphate crosslinker is too low, there will be free liquid, and a semi-solid electrolyte cannot be formed, which is prone to battery leakage and safety problems. As a preferred embodiment of the present invention, the molar ratio of the pyrophosphate crosslinker to the acrylate monomer is (0.5-2):1, such as 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1.0:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1; preferably 1:1.

[0042] As a preferred embodiment of the present invention, the electrolyte is an ester liquid electrolyte. Specifically, the ester liquid electrolyte includes a metal salt and an ester solvent, wherein the metal salt can be selected from at least one of a sodium salt and a lithium salt; and the ester solvent can be selected from at least one of dimethyl carbonate, ethyl acetate, diethyl carbonate, propylene carbonate, and ethylene carbonate.

[0043] The amount of electrolyte should be limited. If the amount of electrolyte is too high, the polymer cannot effectively wrap the liquid electrolyte, free liquid exists, and a semi-solid electrolyte cannot be formed. Battery leakage is prone to occur, causing safety problems. In addition, if the amount of electrolyte is too high, the proportion of phosphorus atoms in the precursor is low, which will affect the flame retardancy and further reduce the safety performance. If the amount of electrolyte is too low, the electrolyte density will increase, affecting the conductivity. As a preferred embodiment of the present invention, the mass fraction of the electrolyte in the precursor is 80% to 95%, such as 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%; preferably 90%.

[0044] The choice of initiator is not limited, as long as it can form free radicals to react with the monomer. As a preferred embodiment of the present invention, the initiator is selected from at least one of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), benzoyl peroxide, and diisopropyl peroxydicarbonate. Further, as a preferred embodiment of the present invention, the initiator is azobisisobutyronitrile.

[0045] The amount of initiator should be limited. When the initiator content is too low, complete curing cannot be achieved and leakage occurs. When the initiator content is too high, the excess initiator does not contribute to the entire electrolyte and does not improve the performance, which is equivalent to introducing impurities. As a preferred embodiment of the present invention, the amount of the initiator is 0.1% to 0.5% of the total amount of the pyrophosphate crosslinker and the acrylate monomer, such as 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, preferably 0.3%.

[0046] The initiator decomposes at a certain temperature to form free radicals, which react with the monomers through free radical polymerization to obtain a semi-solid electrolyte. As a preferred embodiment of the present invention, the initiation temperature is 40 to 80°C, preferably 50 to 70°C, preferably 55 to 65°C, such as 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, preferably 60°C.

[0047] at last Another object of the present invention is to provide a battery using the semi-solid electrolyte. The battery is prepared by the following steps: after assembling the electrolyte precursor into an ion battery, polymerizing at an initiation temperature to obtain a semi-solid battery.

[0048] As a preferred embodiment of the present invention, the battery is prepared by the following steps: coating the positive electrode active material, conductive material, and binder on the current collector and then drying to obtain the positive electrode; installing the positive electrode and the negative electrode into the battery shell; injecting the precursor into the battery shell and sealing it; and polymerizing at the initiation temperature to obtain a semi-solid battery.

[0049] As a preferred embodiment of the present invention, the positive electrode active material includes at least one of sodium vanadium phosphate, sodium iron phosphate, lithium cobaltate, and lithium iron phosphate, preferably sodium vanadium phosphate; the conductive material includes at least one of carbon black and conductive graphite, preferably carbon black; the binder includes at least one of PVDF and C-PVDF, preferably PVDF.

[0050] Beneficial effects of the present invention:

[0051] 1. The present application provides a pyrophosphate crosslinking agent and a preparation method thereof. The pyrophosphate can be used in semi-solid electrolytes to provide good flame retardant properties and electrical properties.

[0052] 2. The present application provides an electrolyte and a battery using the above-mentioned pyrophosphate cross-linking agent. The obtained electrolyte has been comprehensively improved in terms of flame retardancy, flexibility, and electrical properties, and the battery made from this electrolyte is non-flammable and has high safety performance; at the same time, the first-week capacity at 0.2C reaches more than 100mAh / g, the capacity retention rate is high after 500 cycles, and it has good electrical properties. DETAILED DESCRIPTION

[0053] The following are specific embodiments of the present invention, and further describe the technical solutions of the present invention, but the present invention is not limited to these embodiments.

[0054] Example 1

[0055] A pyrophosphate crosslinking agent , is a compound with the following structural formula (n=0, R is hydrogen):

[0056]

[0057] This pyrophosphate crosslinker is prepared by the following steps:

[0058] S1. The deacidifier is triethylamine, and the raw materials are ethylene glycol and acryloyl chloride. At 4°C, 0.15 mol of ethylene glycol is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.1 mol of triethylamine, and 0.1 mol of acryloyl chloride is slowly added dropwise, and stirring is continued until the acryloyl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final intermediate product acryloyl hydroxyethyl ester.

[0059] S2. The acid scavenger is triethylamine. At 4°C, 0.3 mol of hydroxyethyl acryloyl is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.2 mol of triethylamine, and 0.05 mol of pyrophosphoryl chloride is slowly added. After the addition is completed, stirring is continued until the pyrophosphoryl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final pyrophosphate crosslinking agent.

[0060] Example 2

[0061] A pyrophosphate crosslinking agent , is a compound with the following structural formula (n=3, R is hydrogen):

[0062]

[0063] This pyrophosphate crosslinker is prepared by the following steps:

[0064] S1. The deacidifier is triethylamine, and the raw materials are tetraethylene glycol and acryloyl chloride. At 4°C, 0.15 mol of tetraethylene glycol is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.1 mol of triethylamine, and 0.1 mol of acryloyl chloride is slowly added dropwise, and stirring is continued until the acryloyl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final intermediate product.

[0065] S2. The acid scavenger is triethylamine. At 4°C, 0.3 mol of the intermediate product is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.2 mol of triethylamine, and 0.05 mol of pyrophosphoryl chloride is slowly added. After the addition is completed, stirring is continued until the pyrophosphoryl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final pyrophosphate crosslinking agent.

[0066] Example 3

[0067] A pyrophosphate crosslinking agent , is a compound with the following structural formula (n=3, R is methyl):

[0068]

[0069] This pyrophosphate crosslinker is prepared by the following steps:

[0070] S1. The deacidifier is triethylamine, and the raw materials are tetraethylene glycol and methacryloyl chloride. At 4°C, 0.15 mol of tetraethylene glycol is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.1 mol of triethylamine, and 0.1 mol of methacryloyl chloride is slowly added dropwise, and stirring is continued until the methacryloyl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final intermediate product.

[0071] S2. The acid scavenger is triethylamine. At 4°C, 0.3 mol of the intermediate product is poured into a mixed solution of 100 mL of tetrahydrofuran and 0.2 mol of triethylamine, and 0.05 mol of pyrophosphoryl chloride is slowly added. After the addition is completed, stirring is continued until the pyrophosphoryl chloride reacts completely; the mixed solution is washed with deionized water and dichloromethane solvent in turn, dried with calcium chloride, the solvent is removed, and column chromatography is used for precise purification to obtain the final pyrophosphate crosslinking agent.

[0072] Example 4

[0073] Semi-solid electrolyte and battery , obtained by the following steps:

[0074] Preparation of electrolyte precursor: 12.300 g of liquid ester electrolyte, 2.672 g (0.0047 mol) of pyrophosphate crosslinker prepared in Example 1, 0.403 g (0.0047 mol) of methyl acrylate, and 0.009 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution. The mass fraction of the electrolyte in the precursor was 80%.

[0075] Battery assembly: 0.8g sodium alum phosphate NVP powder, 0.1g carbon black, and 0.1g PVDF were added to an agate mortar, and then an appropriate amount of NMP solvent was added to grind evenly; then the slurry was evenly coated on the surface of aluminum foil (i.e., positive electrode current collector) and vacuum dried at 60°C for 12h, and the dried electrode sheet was cut into discs with a diameter of 12mm, and the positive electrode was obtained after compaction. The button cell was assembled with the sodium sheet as the counter electrode and the above-mentioned semi-solid electrolyte precursor solution as the electrolyte.

[0076] Curing of the electrolyte: The assembled battery was heated and cured at 60°C for 1 hour to obtain the final semi-solid battery.

[0077] Example 5

[0078] This embodiment is substantially the same as embodiment 4, except that the molar ratio of the pyrophosphate crosslinking agent to methyl acrylate is 0.5:1.

[0079] Specifically, 12.300 g of liquid ester electrolyte, 2.362 g (0.0041 mol) of the pyrophosphate crosslinking agent prepared in Example 1, 0.713 g (0.0083 mol) of methyl acrylate, and 0.009 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution.

[0080] Example 6

[0081] This embodiment is substantially the same as embodiment 4, except that the molar ratio of the pyrophosphate crosslinking agent to methyl acrylate is 2:1.

[0082] Specifically, 12.300 g of liquid ester electrolyte, 2.859 g (0.0050 mol) of the pyrophosphate crosslinking agent prepared in Example 1, 0.216 g (0.0025 mol) of methyl acrylate, and 0.009 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution.

[0083] Example 7

[0084] This embodiment is basically the same as Embodiment 4, the only difference being that the mass fraction of the electrolyte in the precursor is 90%.

[0085] Specifically, 13.838 g of liquid ester electrolyte, 1.336 g (0.0023 mol) of the pyrophosphate crosslinking agent prepared in Example 1, 0.202 g (0.0023 mol) of methyl acrylate, and 0.005 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution.

[0086] Example 8

[0087] This embodiment is basically the same as Embodiment 4, the only difference being that the mass fraction of the electrolyte in the precursor is 95%.

[0088] Specifically, 14.606 g of liquid ester electrolyte, 0.668 g (0.0012 mol) of the pyrophosphate crosslinking agent prepared in Example 1, 0.101 g (0.0012 mol) of methyl acrylate, and 0.002 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution.

[0089] Example 9

[0090] Semi-solid electrolyte and battery , obtained by the following steps:

[0091] Preparation of electrolyte precursor: 13.838 g of liquid ester electrolyte, 1.426 g (0.0013 mol) of pyrophosphate crosslinker prepared in Example 2, 0.112 g (0.0013 mol) of methyl acrylate, and 0.005 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution. The mass fraction of the electrolyte in the precursor was 90%.

[0092] Battery assembly: 0.8g sodium alum phosphate NVP powder, 0.1g carbon black, and 0.1g PVDF were added to an agate mortar, and then an appropriate amount of NMP solvent was added to grind evenly; then the slurry was evenly coated on the surface of aluminum foil (i.e., positive electrode current collector) and vacuum dried at 60°C for 12h, and the dried electrode sheet was cut into discs with a diameter of 12mm, and the positive electrode was obtained after compaction. The button cell was assembled with the sodium sheet as the counter electrode and the above-mentioned semi-solid electrolyte precursor solution as the electrolyte.

[0093] Curing of the electrolyte: The assembled battery was heated and cured at 60°C for 1 hour to obtain the final semi-solid battery.

[0094] Example 10

[0095] Semi-solid electrolyte and battery , obtained by the following steps:

[0096] Preparation of electrolyte precursor: 13.838 g of liquid ester electrolyte, 1.431 g (0.0012 mol) of pyrophosphate crosslinker prepared in Example 3, 0.107 g (0.0012 mol) of methyl acrylate, and 0.005 g of AIBN were mixed to obtain a semi-solid electrolyte precursor solution. The mass fraction of the electrolyte in the precursor was 90%.

[0097] Battery assembly: 0.8g sodium alum phosphate NVP powder, 0.1g carbon black, and 0.1g PVDF were added to an agate mortar, and then an appropriate amount of NMP solvent was added to grind evenly; then the slurry was evenly coated on the surface of aluminum foil (i.e., positive electrode current collector) and vacuum dried at 60°C for 12h, and the dried electrode sheet was cut into discs with a diameter of 12mm, and the positive electrode was obtained after compaction. The button cell was assembled with the sodium sheet as the counter electrode and the above-mentioned semi-solid electrolyte precursor solution as the electrolyte.

[0098] Curing of the electrolyte: The assembled battery was heated and cured at 60°C for 1 hour to obtain the final semi-solid battery.

[0099] Comparative Example 1

[0100] This comparative example is basically the same as Example 4, except that the electrolyte is 15.375 g of liquid ester electrolyte.

[0101] Comparative Example 2

[0102] This comparative example is basically the same as Example 4, except that the pyrophosphate crosslinking agent prepared in Example 1 is replaced by a phosphate having the following structural formula in the prior art:

[0103]

[0104] Comparative Example 3

[0105] This comparative example is basically the same as Example 4, except that the pyrophosphate crosslinking agent prepared in Example 1 is replaced by a phosphate having the following structural formula in the prior art:

[0106]

[0107] Comparative Example 4

[0108] This comparative example is basically the same as Example 4, except that the pyrophosphate crosslinking agent prepared in Example 1 is replaced by a phosphate having the following structural formula in the prior art:

[0109]

[0110] Battery performance test: The batteries obtained in Examples 4 to 10 and Comparative Examples 1 to 4 were subjected to electrical performance tests; the obtained batteries were disassembled, and a combustion test was performed on the disassembled separator and electrolyte mixture; the test results are shown in Table 1 below.

[0111] Table 1.

[0112]

[0113] As shown in Table 1, the first-week capacity of the batteries obtained in Examples 4 to 10 all reached more than 100 mAh / g, the capacity retention rate all reached more than 92%, and the degree of combustion was not large, proving that the electrolyte and battery prepared by the cross-linking agent of the present application have good electrical properties and flame retardant properties.

[0114] By comparing Example 4 and Comparative Example 1, it can be seen that the semi-solid electrolyte has significantly improved flame retardancy and cycle performance (capacity retention rate after 500 cycles) compared with the liquid electrolyte. This is because there is no flame retardant component in the liquid battery pack and the degree of combustion is greater; the liquid electrolyte is more likely to have side reactions with the electrode, thereby reducing the cycle performance of the battery.

[0115] By comparing Example 4 with Comparative Examples 2, 3, and 4, it can be seen that the electrolyte and battery prepared by the pyrophosphate crosslinker of the present application have advantages in flame retardancy and electrical properties compared to the phosphates of the prior art. This may be because the present application removes the spiro ring in the structure while retaining the symmetrical structure and the diphosphorus atom (or diphosphate structural fragment). Compared with Comparative Example 2, the present application eliminates the adverse effects of the spiro ring on charge movement and improves electrical properties. Compared with Comparative Example 3, the present application not only eliminates the adverse effects of the asymmetric structure on endothermic flame retardancy and improves flame retardancy; and the structure of the present application is non-acidic, thereby improving the cycle performance of the battery. Compared with Comparative Example 4, the flame retardant structural fragment of the present application accounts for a high proportion and improves flame retardancy.

[0116] In addition, in the examples, by comparing Example 4 with Examples 5 and 6, it can be seen that the molar ratio of the cross-linking agent to the monomer is different, and the difference in the first-week capacity is not large. This is because: the ion transport of the semi-solid electrolyte can be transmitted in two forms. One is the three-dimensional network structure formed by the polymer, which can transport ions in the form of coordination (same as the all-solid polymer electrolyte); the second is the electrolyte wrapped inside, which is still flowable at the microscopic level, so it can be transported in the form of a liquid electrolyte; regardless of the degree of cross-linking, ion transport can be achieved, so it has little effect on the first-week capacity electrical performance. There is a difference in the capacity retention rate after 500 cycles. This is because: the insufficient degree of cross-linking in Example 5 causes the electrolyte to have free liquid and closer to the performance of a liquid electrolyte, so as mentioned above, it is easy to react with the electrode, thereby reducing the cycle performance of the battery. In Example 6, the degree of cross-linking is high, the electrolyte elasticity and toughness are insufficient, and the stability is poor, resulting in a decrease in the capacity retention rate after 500 cycles.

[0117] By comparing Example 4 with Examples 7 and 8, it can be seen that the change in the proportion of the liquid ester electrolyte has little effect on the electrical properties. This is because, as mentioned above, the ion transport of the semi-solid electrolyte can be transmitted in the form of polymers and liquid electrolytes. Since both polymers and electrolytes can achieve ion transport, the proportion of the liquid electrolyte has little effect on the electrical properties. However, the proportion of the liquid ester electrolyte affects the proportion of the phosphate flame retardant fragments, and therefore affects the flame retardant effect. When the mass proportion of the liquid ester electrolyte in the precursor does not exceed 90%, the flame retardant performance reaches the best. Furthermore, under the condition of ensuring flame retardant performance, when the mass of the liquid ester electrolyte in the precursor is 90%, the electrical performance of the battery also reaches the best. This may be due to the relatively high ion transport effect of the liquid electrolyte relative to the polymer.

[0118] By comparing Example 7 and Example 9, it can be seen that when n increases, the capacity retention rate increases, which may be because the ethoxy segment is conducive to the transmission of ions.

[0119] By comparing Example 9 and Example 10, it can be seen that the difference in R groups has no significant effect on the electrical properties.

[0120] The specific embodiments described herein are merely examples of the spirit of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in similar ways, but they will not deviate from the spirit of the present invention or exceed the scope defined by the appended claims.

Claims

1. A pyrophosphate crosslinking agent, characterized in that: It is a compound with the following general structural formula: Wherein, n is a natural number and n≥0; R is hydrogen or methyl.

2. A pyrophosphate crosslinking agent according to claim 1, characterized in that: n=3。 3. A method for preparing a pyrophosphate crosslinking agent as claimed in any one of claims 1 to 2, characterized in that: The following steps are involved: S1. In the presence of an acid scavenger, reacting an ethylene glycol compound and an acryloyl chloride compound in a solvent to obtain an intermediate product; S2. In the presence of an acid scavenger, reacting the intermediate product with pyrophosphoryl chloride in a solvent to obtain the pyrophosphate crosslinking agent.

4. The method for preparing a pyrophosphate crosslinking agent according to claim 3, characterized in that: The molar ratio of the ethylene glycol compound, the acryloyl chloride compound and the acid scavenger is (1.1-2):1:

1.

5. The method for preparing a pyrophosphate crosslinking agent according to claim 3, characterized in that: The molar ratio of the intermediate product, pyrophosphoryl chloride and the acid scavenger is (2.5-3.5):0.5:

2.

6. The method for preparing a pyrophosphate crosslinking agent according to claim 3, characterized in that: The reaction environment temperatures of steps S1 and S2 are respectively 0-10°C.

7. A semi-solid electrolyte, characterized in that: The semi-solid electrolyte is prepared by the following steps: mixing the pyrophosphate crosslinking agent as claimed in any one of claims 1 to 2 with an acrylate monomer, an electrolyte and an initiator to obtain a precursor, and initiating a polymerization reaction of the precursor to obtain the semi-solid electrolyte.

8. A semi-solid electrolyte according to claim 7, characterized in that: The molar ratio of the pyrophosphate crosslinking agent to the acrylic ester monomer is (0.5-2):

1.

9. A semi-solid electrolyte according to claim 7, characterized in that: The mass fraction of the electrolyte in the precursor is 80% to 95%.

10. A battery, characterized in that: Comprising the semi-solid electrolyte as claimed in any one of claims 7 to 9.

Citation Information

Patent Citations

  • Secondary battery comprising electrolyte additive

    CN104380519A

  • Negative electrode for secondary battery, and secondary battery comprising same

    CN104380504A

  • Preparation method of all-solid-state polymer electrolyte and secondary lithium battery containing electrolyte

    CN107785609A

  • Phosphate cross-linking agent and preparation method thereof, phosphate-based cross-linked gel polymer electrolyte and preparation method and application thereof

    CN111499663A

  • Pyrophosphoric ester derivative

    JP1982131799A